Replacing the Content in e-Abacus Diagram II - Mahmood, Ammar Seddiq; Basher, Fatmah Ahmed (Iraqi Journal of Science, 2021)
In our normal life, we sometimes need a process of replacing something with another to get out of the stereotype. From this point of view, Mahmood’s attempted in the year 2020 to replace the content in the first main e-abacus diagram. He found the general rule for finding the value of the new partition after the replacement from the original partition. Here we raise the question: Can we find the appropriate mechanisms for the remainder of the main e-abacus diagram?